Diseases associated with growth hormone deficiency and short stature in Maternity and Child Teaching Hospital in Al-Diwaniyah Province, Iraq - Khayoon Hammood Alyasiry, Qahtan; Mahdi Hussain, Moayed; Nasir AlObaidi, Jomah (International Journal of Psychosocial Rehabilitation, 2020)
Background: One of the principal health parameters in children are growth and stature progress. One of frequent health issues in every day pediatric practice is the problem of short stature. The interplay among a multitude of processes and events determine the stature and growth in children including functioning endocrine system, genetic predisposition, effects of chronic diseases, nutritional status and level of physical activity. There is little if any information about the prevalence and nature of short stature in Al-Diwaniyah province, mid-Euphrates region of Iraq.Aim of the study: the current study was aiming at highlighting the commonest causes and patterns of short stature in this province.Patients and methods: Assessment of children height was done with standing position against wall-mounted, without foot ware, heels and back touching the wall, the child looking straight ahead, gentle but firm pressure upwards applied to the mastoid underneath with assessment of upper segment (US)/ lower segment (LS) ratio. Assessment of father and mother height was also carried out.Results: The most frequent cause was mall for gestational age which was seen in 38 (27.9) cases, followed by chronic medical illness in 28 (20.6 %) cases and celiac disease in 26 (19.1 %) cases. Other causes included hypothyroidism in 17 (12.5 %), Genetic (isolated GH deficiency) in 13 (9.6 %), Congenital adrenal hyperplasia in 8 (5.9 %), Turner syndrome in 8 (5.9 % and Prader Willi syndrome in 2 (1.5 %). Chronic medical illnesses included: bronchial asthma, epilepsy, chronic constipation, recurrent UTI, chronic diarrhea, sickle cell anemia and thalassemia.Conclusion: Small for gestational age, chronic medical illness and celiac disease were the principal causes of short stature in Al-Diwaniyah province.